Development of a robust and sustainable Malaysian Integrated Ocean Observation System - Mohd Rizal, Arshad, Engr. Assoc. Prof. Dr.; Khalid, Isa; Herdawatie, Abdul Kadir (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org